1996
DOI: 10.1074/jbc.271.50.32021
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of Inositol 1,4,5-Trisphosphate/Ca2+-induced Cl− Currents by Prolonged Activation of G Proteins in Xenopus Oocytes

Abstract: Expression of G protein ␣ subunits of the G q family with various G protein-coupled receptors induces activation of an inositol 1,4,5-trisphosphate (IP 3 )/Ca 2؉ -mediated Cl ؊ conductance in Xenopus oocytes. Our present data show that two members of this family, the human G␣ 16 subunit and the murine homologue G␣ 15 , can induce both activation and inhibition of these agonistinduced currents. Although extremely low amounts (10 -50 pg) of injected G␣ 16 subunit cRNA cause modest (ϳ2-fold) enhancement of ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…This result was similar to that previously jpet.aspetjournals.org observed in oocytes expressing the thyrotropin-releasing hormone receptor and ␣ subunits of the Gq family G 16 (Quick et al, 1996). They suggested that overexpressed free ␣ subunits activated phospholipase C and desensitized the pathway.…”
Section: Discussionsupporting
confidence: 79%
“…This result was similar to that previously jpet.aspetjournals.org observed in oocytes expressing the thyrotropin-releasing hormone receptor and ␣ subunits of the Gq family G 16 (Quick et al, 1996). They suggested that overexpressed free ␣ subunits activated phospholipase C and desensitized the pathway.…”
Section: Discussionsupporting
confidence: 79%
“…3D). Concentrations of the three basic amino acids at 3 M elicited no response, and higher concentrations (300 M) led to decreased currents compared with 100 M (data not shown) presumably because of desensitization of the receptor and/or the signaling pathway proteins, as reported by others (Minakami et al, 1994;Quick et al, 1996). L-Arg, L-Lys, and L-Orn were thus the most potent agonists tested, showing that the receptor has a preference for basic amino acids.…”
Section: Deorphanization Of Gprc6a 593mentioning
confidence: 58%
“…In our experiments, injections of the cRNAs coding G␣ q family members (0.5-40 ng) always inhibited ginsenoside-induced Cl Ϫ current; we never detected enhancement of the oocyte response even at very low doses of the cRNAs. The reason Quick et al (17) observed enhancement of the oocyte response after injections of smaller doses of G␣ q or G␣ 16 cRNA might be simply that they co-injected TRH receptor cRNA. In this case, the exogenously expressed G␣ q or G␣ 16 might couple to co-expressed TRH receptors, increasing the efficacy of TRH in inducing the Cl Ϫ current.…”
Section: Fig 4 Increase In Ginsenoside-induced CLmentioning
confidence: 99%
“…Recently, Quick et al (17) reported that in the Xenopus oocyte, expression of a G␣ q family member (G␣ q or G␣ 16 ) significantly altered the amplitude of thyrotropin-releasing hormone (TRH)-induced Cl Ϫ current. This report coupled with the present findings points to the possibility that ginsenosides and TRH share the same signal transduction pathways.…”
Section: Fig 4 Increase In Ginsenoside-induced CLmentioning
confidence: 99%